Research of local deformation processes of the Dniester PSPP territory at 2010–2015 - Savchyn, Ihor; Vovk, Andriy; Vaskovets, Serhii (Lviv Polytechnic Publishing House, 2016)
The parameters of horizontal earth crust deformation on the Dniester PSPP territory for the period (2010–2015) were calculated. Using obtained data, maps of dilation velocity distribution were constructed. It was found that the epicenters of extreme values of dilation velocity distribution coincide with the construction site of the main elements of the objects. Calculated parameters of horizontal crustal deformation and built by these parameters maps prove significant deformation processes in studied region which connected with construction work and starting of first and second hydropower units. Established that automated deformation monitoring system must be deployed at the Dniester PSPP territory.
Keywords: geodynamic researches; local deformation; deformation parameters; dilatation; GNSS; Dniester PSPP